Variations in keratometric values (K‐value) after administration of three different eye drops – effects on the intraocular lens calculations in relation to cataract surgery. Issue 6 (18th March 2020) - Jensen, Mia N.; Søndergaard, Anders Peter; Pommerencke, Claus; Møller, Flemming
Abstract: Purpose: To investigate the variance in keratometric ( K ) values after administration of different eye drops (three tested), and the effects on intraocular lens (IOL) power calculations in relation to standard cataract surgery. Methods: A prospective intervention study (pilot study) on 38 participants (22 women, 16 men, 58–88 years) undergoing 57 cataract surgeries. Three keratometries on each eye were performed: a baseline ('standard') keratometry about 9 weeks preoperatively, and two on the operation day; a 'dry'‐measurement before interventions and a 'wet'‐measurement after applying one of three eye drops (saline, Systane Ultra ®, or Systane Complete ® ). All standard cataract operations were uneventful. Variabilities in K ‐values, spherical equivalents (SEQs) for IOL power calculations (Barrett TK Universal II) and subjective manifest refractions (SRs) 6 weeks postoperatively were compared between groups. Results: The 'wet' K ‐values had a similar variability to those of the 'standard' and 'dry' K ‐values (p > 0.05, anova on ranks). The mean paired differences in K ‐measurements between groups ranged within a small interval from −0.0107 to 0.0096 mm. After comparing the SEQ predictions with SR‐measurements, the most precise IOL calculation was achieved after administration of a saline eye drop, but the precision was not statistically improved compared to the other drop modalities. Conclusion: The variability in K ‐values was not significantly changed by administration of any of the different eye drops tested, suggesting that artificial eye drops do not impact the keratometry or IOL power prediction.